Mapping Interventions for Adolescent Mental Health: A Scoping Review Across Multiple Settings and Approaches - Wahyuni, Fani Cahya; Ulfatul Karomah; Annisa Asti Pratiwi; Anindita Dwi Hapsari; Ray Wagiu Basrowi; Dela Riadi (Universitas Airlangga, 2025)
Background: According to the World Health Organization (WHO), one in seven adolescents aged 10–19 years has experienced a mental disorder. In the United States, adolescents report symptoms of anxiety and depression, while in Southeast Asia, many students feel lonely, excessively worried to the point of disturbed sleep, and lack close friends. Multiple factors, including psychosocial and environmental elements, influence adolescent mental health. There is a growing need for culturally appropriate education and support programs tailored to Indonesian adolescents. Various factors can affect adolescent mental health. Indonesian adolescents need culturally appropriate mental health education and support programs. Objective: This study aims to examine mental health programs based on school, digital platform, community, and healthcare settings. Methods: This scoping review analyzed mental health programs worldwide from 2015-2025. The PRISMA diagram was used as a selection flow where 34 articles met the inclusion criteria, obtained from three databases (PubMed, Science Direct, SpringerLink), and selected from 649 articles. Results: Most mental health programs were delivered through school-based, digital, community, and healthcare settings. These programs employed innovative approaches for promotion, prevention, and treatment. Key outcomes included improvements in mental health and overall well-being. Several programs were found to be effective, feasible, and acceptable among adolescents. Program selection should address the core mental health issue, such as anxiety or depression. Multi-sectoral collaboration is crucial for ensuring the sustainability and effectiveness of adolescent mental health programs. Future literature reviews should focus on specific mental health issues to enable deeper analysis and more targeted recommendations